Holy Spirit and Ghost：From Truth to Dictatorship - LI, Ling (Journal of Research for Christianity in China (JRCC), 2025)
This paper focuses on how truth and power have been combined in the history of Western Christianity, eventually leading to the sanctification of power and the power of truth. Once a certain truth is sanctified, it can easily be adopted as an absolute dogma and become a tool to destroy dissenters or even kill people, becoming a "ghost" wandering over the heads of the people. Therefore, the pursuit of truth is a legitimate act, but using the so-called truth as a tool to consolidate power and maintain dictatorship is not desirable.